Penguatan Soft Skills Siswa SMK Farmasi Saraswati 3 Denpasar melalui Sosialisasi Nilai-Nilai Kaizen dan Budaya 5S - Ni Luh Gede Meilantari; Tomas Falnilius Pulo; Ni Nyoman Widyastuti (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
This community service program aims to enhance the soft skills among students at SMK Farmasi Saraswati 3 Denpasar through socialization activities. The program focuses on core values of Japanese work culture: Kaizen (continuous improvement), 5S (seiri, seiton, seiso, seiketsu, shitsuke: sort, set in order, shine, standardize, sustain). These values are highly relevant to the pharmaceutical profession which demands precision, cleanliness, discipline, responsibility and excellent patient service. The activity involved 50 students from the eleventh grade, selected based on their readiness for upcoming workplace internships. The implementation consisted of three main stages: preparation, execution and evaluation. During the execution stage, students participated in interactive lectures, a 5S simulation exercise and a discussion session. Data were collected through observation sheets and participant satisfaction questionnaires. The result showed that the student participation and enthusiasm wre high, with 87% of students actively engaging in discussions and simulation activities. The 5S simulation successfully demonstrated the practical application of work culture values in a pharmacy laboratory setting. In conclusion, socialization is an effective and engaging method for improving vocational students’ appreciation of Japanese work culture, thereby better preparing them for the professional world. Recommendation is provided for schools to integrate these Japanese work value into their regular curricula and for further research with extender implementation time.